2018
DOI: 10.1042/bsr20171035
|View full text |Cite|
|
Sign up to set email alerts
|

Atorvastatin ameliorates early brain injury through inhibition of apoptosis and ER stress in a rat model of subarachnoid hemorrhage

Abstract: Aneurysmal subarachnoid hemorrhage (SAH) is a severe cerebrovascular disease with very poor prognosis. The aim of the present study was to evaluate the protective effects of atorvastatin on early brain injury (EBI) after SAH using a perforation SAH model. Male Sprague–Dawley rats were randomly divided into four groups: the sham group, the SAH group (model group), SAH + 10 mg.kg−1.day−1 atorvastatin (low atorvastatin group), and SAH + 20 mg.kg−1.day−1 atorvastatin (high atorvastatin group). Atorvastatin was adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 30 publications
3
18
0
Order By: Relevance
“…Our results showed that atorvastatin treatment significantly reduced caspase‐3 expression and this is in accordance with studies of Ref. [65–67]. Yang et al suggested that reduction in caspase‐3 expression by atorvastatin may be via increasing the phosphorylation of Akt1 during ischemia/reperfusion [66].…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that atorvastatin treatment significantly reduced caspase‐3 expression and this is in accordance with studies of Ref. [65–67]. Yang et al suggested that reduction in caspase‐3 expression by atorvastatin may be via increasing the phosphorylation of Akt1 during ischemia/reperfusion [66].…”
Section: Discussionsupporting
confidence: 92%
“…Caspase as a family of cysteine proteases that play an important part in apoptosis. Caspases-3 influences the process of neuronal apoptosis, and has a correlation with patient prognosis and mortality [14,15]. A total of 6 rabbits from each group were assessed.…”
Section: Methodsmentioning
confidence: 99%
“…Endoplasmic reticulum (ER) stress is believed to exert important roles in EBI . Glucose‐regulated protein 78 (GRP78), which belongs to HSP70 family, is mainly localized in the ER Acting as a chaperone that folds and transports proteins, GRP78 can bind to three ER sensors, protein kinase RNA‐like ER kinase (PERK), activating transcription factor 6 (ATF6), and inositol‐requiring protein 1α (IRE1) .…”
Section: The Pathophysiology Of Sahmentioning
confidence: 99%
“…The alleviation of delayed vasospasm does not improve the clinical outcome in patients with SAH, which leads to a reasonable doubt as to whether delayed cerebral vasospasm affects the prognosis of SAH . Therefore, an increasing number of scholars have begun to support the theory that EBI is the chief cause of mortality and disability following SAH …”
Section: The Pathophysiology Of Sahmentioning
confidence: 99%